A landmark in the history of science: H. von foerster’s cybernetics of cybernetics (1974) (2020)
This paper presents and discusses an authentic landmark in the history of science, namely H. v. Foerster’s Cybernetics of Cybernetics, 1974, a most fundamental book based on the students’ notes. This is a book rarely known even by many specialists. This paper claims that von Foerster’s book constitutes a unique achievement in the history of science and pro-vides reasons. A thorough presentation is introduced that brings a complete panorama of concepts, problems and approaches